Carotid Artery Stenosis Contralateral to Intracranial Large Vessel Occlusion: An Independent Predictor of Unfavorable Clinical Outcome After Mechanical Thrombectomy - Maus, Volker; Abdullayev, Nuran; Sack, Henrik; Borggrefe, Jan; Mpotsaris, Anastasios; Behme, Daniel (Frontiers in Neurology, 2018)
Background Clinical outcome in patients undergoing mechanical thrombectomy due to intracranial large vessel occlusion in the anterior circulation is influenced by several factors. The impact of a concomitant extracranial carotid artery stenosis (CCAS) contralateral to the intracranial lesion remains unclear. Methods Retrospective analysis of prospectively collected data of two comprehensive stroke centers between 2014 and 2017. Three hundred and ninety-two consecutive patients with intracranial vessel occlusion in the anterior circulation were treated with thrombectomy. Clinical (including demographics and NIHSS), imaging (including angiographic evaluation of CCAS via NASCET criteria), and procedural data were evaluated. Primary endpoint was an unfavorable clinical outcome defined as modified Rankin Scale 3-6 at 90 days. Results In 27/392 patients (7%) pre-interventional imaging exhibited a CCAS (>50%) contralateral to the intracranial lesion compared to 365 patients without relevant stenosis. Median baseline NIHSS, procedural timings, and reperfusion success did not differ between groups. Median volume of the final infarct core was larger in CCAS patients (176 cm3, IQR 32-213 vs. 11 cm3, 1-65; p<0.001). At 90 days, unfavorable outcome was documented in 25/27 CCAS patients (93%) vs. 211/326 (65%; p=0.003) with a mortality of 63% vs. 19% (p=0.001), respectively. Presence of CCAS was associated with an unfavorable outcome at 90 days independent of age and baseline NIHSS in multivariate logistic regression (OR 2.2, CI 1.1-4.7; p<0.05). Conclusion For patients undergoing MT due to intracranial vessel occlusion in the anterior circulation, the presence of a contralateral CCAS >50% is a predictor of unfavorable clinical outcome at 90 days.